Perlindungan Hukum Bagi Pemilik Karya Cipta Batik Tulis Dewi Rengganis Di Desa Jatiurip Kecamatan Krejengan Kabupaten Probolinggo - Nuzulia Kumala Sari; Dyah Ochtorina Susanti (SASI, 2018)
This research background by the existence of Dewi Rengganis Batik which is the characteristic of Jatiurip Village, Krejengan District, Probolinggo Regency, where each batik motif tells about the figure of Dewi Rengganis who is the daughter of Prabu Brawijaya from the Majapahit Kingdom, but the batik has not been registered. This resulted in the owner of Batik Dewi Rengganis not getting legal protection. The results of this study using normative Legal Research with statute approach and conceptual approach are to provide an explanation and understanding of the importance of copyright registration to protect the copyrighted works of Batik Dewi Rengganis, and  describe  legal  protection  for  owners  of Batik Dewi Rengganis works in Jatiurip Village, Krejengan District Probolinggo Regency.